Pengaruh Kompetensi Profesional Guru Terhadap Minat Belajar Siswapada Mata Pelajaran TIKdi MTSN2 Tapanuli Tengah - Sitompul, Sonia Widya Ulfa Sitompul; Efriyanti, Liza; Okra, Riri; Aprison, Wedra (Indonesian Research Journal on Education, 2023)
The purpose of the studywas to determine whether or not there was an influence of teacher professional competence on student interest in learning at MTsN 2 Tapanuli Tengah. The background of the research is that teachers who teach ICT are not original teachers in the field of ICT, teachers do not maximize the use of technology and when explaining the teacher only explain the important points that make students not really listen so that when there is a practical assignment, students are confused and finally students ask for help from a smart friend. The type of research used is quantitative correlation. The population is all class VII while the sample is taken using purposive sampling technique. So the sample is 30 students where 15 students are class VII A and 15 class VII B. Theinstrument used is a questionnaire and has been tested for validity and reliability. The test results of the two variables are the validity test of rcount>rtable which means valid and the reliability test of variable X is 0.924> 0.70 and Variable Y is 0.902>0.070 which means reliable. The results of the study where the hypothesis H1 was accepted and H0 was rejected with a sig (2-tailed) value of 0.000>0.005, person correlation 0.837 < 0.361, and r-square 0.700. This means that the professional competence of teachers has a positive influence on students' interest in learning by 70%. Although not a real ICT teacher, as long as the teacher tries to teach as professionally as possible, students' interest in learning will increase. So the teacher should add interesting media that can be taken home so that students can study anywhere and anytime.